EFFECTS OF PROGRESSIVE LOADS WORKOUTS ON THE DEVELOPMENT OF MUSCLE STRENGHT AND BODY COMPOSITION FOR WOMEN - Ghervan O; Leuciuc F (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Special literature shows that High Intensity Interval training (HIIT) has the capacity to develop muscle mass, muscle strength and sports performance. The general recommendation of moderate to high intensity programs using short rest periods was based on empirical evidence suggesting that this training paradigm is commonly used by bodybuilders in the hypertrophy phases of periodic workout for athletes and on studies that have reported higher increases in muscle mass as training volume, meaning the number of the performed sets. If we apply a progressive load training program aiming at improving muscle strength, muscle mass, and body composition changes, we will probably get improvements of these parameters. Thus, this type of protocol could be an effective solution in combating obesity and associated pathologies, which have a weight and an altered body composition complemented by a sedentary life. The exercise program covers a volume and an intensity helping to keep muscle mass, increase in strength and change body composition in the shortest time spent in the fitness gym.